Latitude, distance offshore and local environmental features as modulators of zooplankton assemblages across the NE Atlantic Shelves Province. (8th January 2018) - Fanjul, Alvaro; Iriarte, Arantza; Villate, Fernando; Uriarte, Ibon; Artiach, Miguel; Atkinson, Angus; Cook, Kathryn
Abstract: Contribution of latitude, distance offshore and environmental factors to variations in zooplankton assemblages across the Northeast Atlantic Shelves Province, from the Bay of Biscay [Bilbao 35 (B35) and Urdaibai 35 (U35)] to the English Channel (Plymouth L4; L4) and the North Sea (Stonehaven; SH), were assessed mainly by redundancy analysis. For coarse zooplankton groups latitude explained the main between-site differences, and meroplankton contributed more than holoplankton. Latitudinal differences were best indicated by contrasting abundances of cirripede larvae and doliolids (most abundant at the lowest latitude sites) and bryozoan and polychaete larvae (most abundant at the highest latitude site). Doliolids were best indicators of temperature-mediated latitudinal differences. The interaction between latitude and distance offshore or salinity and phytoplankton biomass explained smaller percentages of the variability. The main differences in copepod and cladoceran genera reflected the oceanic influence, with highest presence of Corycaeus and Oncaea at L4, likely related to the higher influence of off-shelf water intrusions, and neritic Acartia dominating at SH, U35 and B35. Podon and Evadne, which decreased from south to north, reflected latitude-related differences driven more by salinity than by temperature. Instances where a single species (e.g. Acartia clausi ) dominated showed common relationships with temperature, consistent with a common thermal niche. Differences in co-generic species dominance between sites depicted the latitudinal gradient.